A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.